Investigation of the Relationship between Early Maladaptive Schemas, Obsessive Beliefs and Personality Traits (Global Journal of Human-Social Science, 2023)
In this study the relationship between early maladaptive schemas obsessive beliefs and personality traits was investigated In addition it was examined how obsessive beliefs and personality traits were affected by early maladaptive schemas according to different socio- demographic variables The sample group of the study consists of 235 female and 91 male 326 people in Turkey
Keywords: early maladaptive schemas; obsessive beliefs; personality traits